STUDY OF GENERATION AND ATTRACTION OF TRIPS IN THE BOGOR DISTRICT - Daagustani, Muhammad; Murtedjo, Tedy (ASTONJADRO, 2020)
Pamijahan District has 15 villages with an area of 80.83 km2, Leuwiliang District has 13 villages with an area of 61.51 km2, Leuwisadeng District which has 8 villages with an area of 34 km2. The increase in population growth and development in the region has also increased the movement of traffic flow into and out of the area, causing several problems especially in reducing the performance of road sections that cause traffic congestion on road sections. This study aims to create a model of the generation and attraction generated by land uses such as the Education Building, Industrial Estate, Hospital, Traditional Market and Supermarket. Located in the three districts. Data processing is done by calculating the method of transportation analysis using MKJI 2017. Then using (Trip Generation Manual) and then modeled in (Saturn Software). The number of Stitches and Pulls in the area studied was obtained a figure of 89,109 trips / hour. With the level of road services with a range of B to F. Then the design of transportation modeling equations in Pamijahan, Leuwiliang and Leuwisadeng districts is Y = 486,678 + 0.707. (X). This proves that if there is no improvement and improvement of road network infrastructure, and efforts to procure an adequate road-based mass public transport system, it will add to the decline in performance of road segments in the region in the future.